The Effect of Reading Literacy and Emotional Intelligence Toward Students’ Learning Outcomes at Silih Nara Elementary School Aceh Tengah District - Masri, Ulta; Sumanti, Sumanti; Syahrin, Alfi; Zahara (LPPM STKIP Kusuma Negara, 2025)
The research aims and focuses on analyzing the effect of reading literacy and Emotional Intelligence toward the learning outcomes of fifth-grade students at SD Negeri 7 Silih Nara, Aceh Tengah Regency. The research methodology used is quantitative study which conducted in the fifth-grade students of SD Negeri 7 Silih Nara, Aceh Tengah Regency. The research instrument used in this research was test. The data was collected from the test of reading literacy and test of Emotional Intelligence. The data was analyzed by using inferential analysis T-test The inferential analysis utilized multiple regression analysis and hypothesis test with T-test, and F-test (ANNOVA). Data processing was performed by using SPSS Version 23. There were two result findings found based on the result of T-test and F-test (ANNOVA). The first result finding of T-test showed that reading literacy has significant effect toward the students’ learning outcomes that showed by sig value was 0.000 (<0.05), but emotional intelligence does not have the effect toward the students’ learning outcomes (0.163 (>0.05)). The second result finding of F-test (ANNOVA), the reading literacy and emotional intelligence analyzed together has significant effect toward students' learning outcomes. The Sig value obtained was .000b. It means that hypothesis was accepted.